A survey of the school libraries and audiovisual centers administered by the Missionary Sisters of the Immaculate Conception with implications for development planning - Gumnad, Ma. Socorro G. (Ma. Socorro Gerdan) 1937- (1987.)
To find out the extent of development of the library and audiovisual centers, the Missionary Sisters of the Immaculate Conception (MIC) administered a survey. The following were considered: statement of objectives, library personnel, budget and sources of financial support, the collection, organization of collection, library/audiovisual programs and services, and the equipment, facilities and quarters. It can be concluded that the school libraries differ in their development in all aspects. Only ICA has defined its purposes and written these in the EMC Manual of Information.
Mimeographed.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Vita.
Keywords: School libraries -- Evaluation. -- Philippines; Audiovisual library service -- Philippines